2018
DOI: 10.22456/1982-8918.73009
|View full text |Cite
|
Sign up to set email alerts
|

A Educação Física E O Trabalho Educativo Inclusivo

Abstract: Analisamos o trabalho educativo nas aulas de Educação Física (EF), discutindo-o na sua relação com os propósitos da inclusão de estudantes com deficiência numa escola regular privada. No geral, alinhamos a investigação com a base teórica crítico-dialética e, nesta, o método da ascensão do abstrato ao concreto elaborado por Kosik (2011). Utilizamos o estudo de caso via estudo documental (o planejamento da professora, o Projeto Político Pedagógico e os perfis da turma) e de campo, tendo como sujeitos: a professo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
3
0
6
Order By: Relevance
“…These are considered a vulnerable population with fewer possibilities than their non-disabled counterparts of entering basic education, staying in it, and enrolling in successive school years. Regarding physical activity of people with disabilities, it is reported that only 33.8% of schoolchildren with disabilities perform any sports or physical activity apart from Physical Education (Jung et al, 2013), according to our knowledge, we have not identified any research within the Mexican context that evaluates physical activity in students with hearing impairment, the above is important as a basis for action by teachers working in the field of Physical Education around people with disabilities (Andrade & Freitas, 2016) and have teaching-learning conditions with inclusive methods (Simões et al, 2018) since the United Nations Educational, Scientific and Cultural Organization (UNESCO), manifests in its guide for policy makers in Physical Education to focus inclusive methodologies aimed at raising awareness about people with disabilities, pro-moting values during Physical Education class, and should also be regulated for promotion among students, parents, and members of the community (Mclennan & Thompson, 2015). Therefore, this research aims to comparatively determine physical activity during Physical Education class, and recess of students with hearing impairment in primary school.…”
Section: Introdutionmentioning
confidence: 84%
“…These are considered a vulnerable population with fewer possibilities than their non-disabled counterparts of entering basic education, staying in it, and enrolling in successive school years. Regarding physical activity of people with disabilities, it is reported that only 33.8% of schoolchildren with disabilities perform any sports or physical activity apart from Physical Education (Jung et al, 2013), according to our knowledge, we have not identified any research within the Mexican context that evaluates physical activity in students with hearing impairment, the above is important as a basis for action by teachers working in the field of Physical Education around people with disabilities (Andrade & Freitas, 2016) and have teaching-learning conditions with inclusive methods (Simões et al, 2018) since the United Nations Educational, Scientific and Cultural Organization (UNESCO), manifests in its guide for policy makers in Physical Education to focus inclusive methodologies aimed at raising awareness about people with disabilities, pro-moting values during Physical Education class, and should also be regulated for promotion among students, parents, and members of the community (Mclennan & Thompson, 2015). Therefore, this research aims to comparatively determine physical activity during Physical Education class, and recess of students with hearing impairment in primary school.…”
Section: Introdutionmentioning
confidence: 84%
“…Os caminhos metodológicos dos estudos analisados, destacam a coletividade e a colaboração na organização de um ensino "inclusivo". Apoiado nos aspectos teóricos da Psicologia Histórico-Cultural, Simões et al (2018) afirmam que para a apropriação do conhecimento, como propósito, existe a necessidade de uma articulação coletiva entre professores, alunos, conhecimentos e metodologias. Nesse sentido, caminhamos para a compreensão que a inclusão escolar tem como essência a garantia da aprendizagem dos sujeitos escolarizados.…”
Section: Fontana; Cruzunclassified
“…Si bien el neoliberalismo es una barrera en sí misma, es posible encontrar en el resto de barreras aspectos que tienen relación con lógicas de competencias y rendición de cuentas, como la falta de instancias institucionales para responder a la diversidad (Dainez & Smolka, 2019) y la prevalencia de instrumentos estandarizados para evaluar la educación (Poblete Melis & Galaz Valderrama, 2018). Esto da cuenta de la preeminencia de la racionalidad neoliberal en educación que afecta la puesta en marcha de procesos inclusivos (Alfaro & Herrera Fernández, 2020;Simões et al, 2018;Fischer, 2019;Pacheco et al, 2019;Gutiérrez & Martínez Fernandéz, 2020).…”
Section: Reflexiones Finalesunclassified